The Role of Teachers in Leveraging TikTok for Educational Instruction and Expression - Amalia, Rindi; Fauzi, Imron; Zawawi, M. Ilmil (Aksara Shofa, 2025)
TikTok has become a significant platform transforming how teachers deliver content and share educational ideas. This study examines the application of teacher professional ethics in using TikTok as a learning tool and educational expression, and its effects on teacher professionalism and student engagement. Using a qualitative descriptive approach through library research, data were analyzed from literature on digital ethics, microlearning pedagogy, and teacher-student interaction. Findings indicate TikTok enables creative, concise, and interactive learning, increasing student motivation. Teachers who apply professional ethics ensuring content integrity, modeling digital behavior, separating personal and professional content, and managing interactions responsibly can optimize the platform’s benefits. Ethical challenges such as privacy, blurred boundaries, and reputational risks persist. Future research should include empirical observation, interviews, and content analysis.